The State of Intermediate Science Education Program of Non-Central School in Bayambang District - Macaraeg, Ela B. (8ISC Abstract Proceedings, 2022)
The main objective of this study sought to answer the following questions: What is the demographic profile of teachers of non-central school in Bayambang District I according to their: highest educational attainment; years in teaching science; trainings/seminars attended in mathematics. What is the extent of availability of the physical facility, equipment tools, teaching materials, books, and library used by the teachers of non-central school in Bayambang District I. What is the level of performance of intermediate pupils in science SY 2018-2019? Is there a significant relationship between the level of performance of the intermediate pupils in science and the demographic profile of teachers? Is there a significant relationship between the level of performance of the intermediate pupils in science across the available physical facility, equipment tools, teaching materials, and books used by the teachers? What development plan can be proposed to enhance the science program? What is the acceptability level of the proposed development plan to enhance the science program? A descriptive-correlational research design was used in this study. The respondents of this study were composed of 126 non-central intermediate science teachers of 21 schools in Bayambang District I, Pangasinan, the School Year 2018-2019. The questionnaire checklist was used as the main data gathering instrument in this study. The results, the majority of the teachers of non-central school in Bayambang District I have Masteral units. Majority of the teachers of non-central school in Bayambang District I have moderately short teaching experience in science. There is moderately available physical facilities and slightly available books and library in non-central school in Bayambang District I. Majority of the intermediate pupils in non-central school in Bayambang District I have only satisfactory performance in Science. The length of service of the teachers in non-central school in Bayambang District I affects the level of performance of the intermediate pupils in Science. Availability of equipment tools and teaching materials affects the level of performance of intermediate pupils. Strength. The master's degree units earned by most of the teachers of non-central school in Bayambang District I and the satisfactory performance of intermediate pupils are considered a core strength. Weaknesses. A few availability of physical facilities, science laboratories, a microscope library, and the moderately short experience of teachers teaching science. Opportunities. Teachers’ professional development. Threat. The availability of a few physical facilities, science laboratories, microscope libraries, and the moderately short experience of teachers teaching science pose a threat. The moderately short experience of teachers teaching science also poses a threat. The study recommends the following: School leaders should provide seminars and trainings for science teachers through INSET, School and District LAC sessions. Administrators should also provide technical assistance to teachers in order to facilitate collaborative teaching and learning process. DepEd should continuously provide equipment tools and teaching materials in every school, as well as school principals should also include purchasing equipment tools in science through MOOE to aid the present availability of aforementioned needed by the science teachers and intermediate pupils. The teachers should keep themselves updated and open with new teachings science by absorbing new information from seminars and training, by keeping the students focused on learning by improvising materials and tools in teaching. On the other hand, the pupils should be given more time and experience with the use of equipment tools and teaching materials, and books and information from credible websites should also be provided to them. The Higher School Officials should continue revising and upgrading the existing educational policies appropriate to the needs of the learners and the teachers as well. With this, future researchers should conduct a similar study but to a larger set of respondents and other subjects as well. Keywords : State of Intermediate Science Education Program